Duas for me and my family - Arshad, Tahira Dr. (Maqbool Books Lahore, 2011)
"Duas for Me and My Family" is a resource that provides specific supplications to seek blessings, protection, and guidance for oneself and loved ones. It typically includes various duas for health, happiness, safety, and unity within the family. Each dua is often accompanied by explanations of its significance, encouraging readers to incorporate these prayers into their daily lives. The book aims to strengthen family bonds and deepen the spiritual connection with Allah, fostering a nurturing and supportive environment through the power of prayer.